AB0253 The Relation between Pain and Inflammation in Early Rheumatoid Arthritis – Long-Term Follow up in the Swedish Population-Based EIRA and SRQ Register. (10th June 2014) - Sandberg, M.E.; Altawil, R.; Alfredsson, L.; Klareskog, L.; Saevarsdottir, S.; Lampa, J.
Abstract : Background: Pain is a hallmark symptom of RA and also widespread pain is relatively common in the disease. In order to optimize the respective pain and immune-suppressive treatment strategies, there is a need for more knowledge on long-term course of relations between pain and objective inflammation after RA diagnosis. Objectives: To investigate the course of correlations between pain, disease activity, inflammation parameters and swollen/tender joints in early RA during clinical long-term follow-up. Methods: We used the cases from a Swedish population-based case-control study; the EIRA study; 1802 incident RA patients aged 18-70 was recruited 1996-2009 and followed in the Swedish Rheumatology Quality register for up to 5 years. We calculated the correlation between pain at diagnosis, 3 months, 6 months, 12 months, 2 years and 5 years and DAS28 and its components at the same time points. Results: The correlation between pain and the inflammation marker ESR decreased after diagnosis and was not statistically significant from 3 months and onwards, a similar pattern was found for the inflammation marker CRP (Figure 1 ). In contrast, the correlation between pain and both tender joint count, swollen joint count and patient global assessment (PGA) increased significantly after diagnosis. Tender joint count was significantly more correlated to pain than swollen joint count (swollen joint count correlation coefficient =0.31 [95%CI: 0.26-0.36] vs. tender joint count correlation coefficient =0.44 [95%CI: 0.40-0.48]). All correlations were very similar over calendar period and age at diagnosis and persisted also when patients not treated by DMARDS at diagnosis were excluded. Conclusions: At diagnosis, pain in RA is correlated to both inflammation and clinical arthritis. Already after three months, our data show a loss of correlation between pain and objective inflammation, whereas we describe a stable and sustained correlation between pain and swollen and tender joints for the whole follow-up period of 5 years. These data corroborate the notion that the uncoupling of pain and inflammation may develop early after diagnosis and treatment initiation, and underscores the importance of a close monitoring of other causes of pain than joint inflammation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2126